1966
DOI: 10.2337/diab.15.7.480
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Neogenesis of Islets of Langerhans in the Mouse

Abstract: The source of the new islets during growth and the effect of aging on the number of islets have been studied in Webster Swiss mice. A combination of methods was employed, including microscopy in vivo, enumeration of the total number of islets, radioautography with H-3-thymidine, and conventional histological technics. The total number of islets in normal mice increases with age until about six months, and then becomes stable or decreases slightly. Radioautographs showed that the cells of the islets are in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1969
1969
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The calculation of new cell birth rate (CBR) was based on [3H]-thymidine labeling indices and the assumption that the S-phase of all 4 islet cell types is 6 hr in length and remains as 6 hr throughout the developmental period. This number was based on the data for B-cells for adult mice as reported by Bunnag (1966) and Logothetopoulos (1972) and for fetal mice reported by Denffer (1970). More recent publication (Swenne, 1982) on cultured fetal rat islet cells further showed that fetal rat B-cell also has a DNA synthesis phase of 6 hr, adding credence to the result of analysis for B-cells in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The calculation of new cell birth rate (CBR) was based on [3H]-thymidine labeling indices and the assumption that the S-phase of all 4 islet cell types is 6 hr in length and remains as 6 hr throughout the developmental period. This number was based on the data for B-cells for adult mice as reported by Bunnag (1966) and Logothetopoulos (1972) and for fetal mice reported by Denffer (1970). More recent publication (Swenne, 1982) on cultured fetal rat islet cells further showed that fetal rat B-cell also has a DNA synthesis phase of 6 hr, adding credence to the result of analysis for B-cells in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Using differential stain and radioautography Bunnag (1966) and Denffer (1970) were the earlier workers who studied the cell proliferation of pancreatic B-cells in rodents. Denffer (1970) showed that [3H]-thymidine labeling indices were highest during the last few days of gestation in mice.…”
Section: Cell Proliferative Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that new lobes, including new islets, are constantly generated in the adult pancreas 13,32 . In contrast, the data presented here support the idea that the number of islets during adult life is fixed, with homeostatic responses (for example, b-cell expansion) being performed by differentiated cells residing in these structural units.…”
Section: Discussionmentioning
confidence: 99%
“…This is in con¬ trast to the studies of Ziegler et al (1974) and Koncz et al (1976) in which rats successfully transplanted with adult islets of Langerhans occasionally relapsed into a diabetic state. This may reflect the decreased ability of adult islets to divide compared with foetal and neonatal tissue (Blum et al 1963) or the absence of grafted duct tissue which may be the source of new ß cells (Bunnag, 1966). Duct tissue is present in the neonatal islet transplants.…”
Section: Discussionmentioning
confidence: 98%